Survey of soil invertebrates in selected industrial, agricultural, residential and forested areas of Isabel, Leyte - Enricuso, Odette B. (Odette B. Enricuso, 2014)
This study is conducted to identify the soil invertebrates and determine their diversity, abundance, order richness and soil physico-chemical factors in the selected areas in Isabel, Leyte. Four land use types (industrial, agricultural, residential and forested areas) were selected for a one-time sampling. The soil corer method was used for a random soil collection in a single 20x20m plot station of each selected areas. Soil analysis which focused on the soil pH, Total N, Organic Matter, Available P, Exchangeable K, soil temperature and moisture, and Total Cu, Cd, Pb as well as air temperature readings were carried out. A total of 1019 soil invertebrates were collected with 15 taxa in the forested area, 13 taxa in agricultural area, 12 taxa in the industrial area and 10 taxa in residential area. Soil analysis results showed that soil pH, total N, Exch K, OM content as well as total Pb and Cd fell under the normal range. The Avail P in forested and industrial areas was below the normal range as well as the soil moisture content in all areas due to factors such as soil pH, temparature, and texture. The total Cu in forested area is relatively high among all the selected land use types. Order Collembola as a rapid-growing invertebrate, recorded the most abundant group among all areas while Order Dermaptera recorded the lowest with its nocturnal behavior. The agricultural site got the highest diversity value while the high order richness and abundance value was in the forest site.